PENGARUH FINANCIAL LITERACY, FINANCIAL KNOWLEDGE, LOCUS OF CONTROL, DAN HEDONISM LIFESTYLE TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA MAHASISWA DI SURABAYA - Dias Nikmatus Sholihah; Yuyun Isbanah (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This study aims to determine the effect of financial literacy, financial knowledge, locus of control, and hedonistic lifestyle on financial management behavior in students in Surabaya. The data type used is quantitative data sourced from primary data through questionnaires. The population in this study is students in Surabaya, including students at State Universities and Private Universities from all over Surabaya, with the category of the highest number of students in each region of 135,998. The sampling technique used snowball sampling, which was taken evenly throughout the Surabaya area, both in North Surabaya, South Surabaya, East Surabaya, West Surabaya, and Central Surabaya, and 220 were obtained as samples in this study. Data were analyzed using multiple linear regression and calculated using IBM SPSS 26. The results showed that financial knowledge significantly and positively affected financial management behavior. Meanwhile, financial literacy, locus of control, and hedonistic lifestyle do not significantly affect financial management behavior. Therefore, students at State Universities and Private Universities in Surabaya are expected to increase their financial literacy, especially related to investment and insurance, so they can better manage their finances